Palang Yudho Dance in the Study of Symbolic Meanings - Aristawati, Rahma; Dwi Sasanadjati, M.Hum., Jajuk (GETER : Jurnal Seni Drama, Tari dan Musik, 2025)
This article aims to analyze the meaning of the symbols contained in several elements in a dance work that represents the wealth of local culture. Palang Yudho dance is based on Dongkrek art which also contains elements of pencak silat, so it can be said that this dance successfully collaborates two local arts inherent in Madiun Regency. The urgency of this research lies in the effort to preserve regional culture whose values can be a source of inspiration. However, in reality, many artists today are starting to forget this aspect. Thus, this research is expected to remind the importance of maintaining cultural values. This research uses qualitative methods with data collection techniques through observation, interviews, and document studies which are then analyzed using Sumandiyo's symbol theory which states that dance as a cultural product is a symbol system used by humans to understand themselves, their environment, and social interactions. The results showed that Palang Yudho Dance contains cultural symbols that reflect the values of protection, safety, and identity of the Madiun people expressed through movements, costumes, music, and properties used. This research emphasizes the importance of preserving local culture as part of regional identity. In addition to contributing to cultural studies, the results of this research are also expected to be a reference for artists and academics in efforts to preserve and develop traditional arts in Indonesia.